Perfil do atendimento odontológico no Serviço de Urgência para crianças e adolescentes da Faculdade de Odontologia de Araraquara (FOAr) ‒ UNESP - Albuquerque, Yasmin Etienne; Zuanon, Angela Cristina Cilense; Pansani, Cyneu Aguiar; Giro, Elisa Maria Aparecida; Lima, Fábio César Braga De Abreu E; Pinto, Lourdes Aparecida Martins Dos Santos; Cordeiro, Rita De Cássia Loiola; Costa, Josimeri Hebling; Brighenti, Fernanda Lourenção (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
Abstract Introduction: Urgency care is a common practice in pediatric dentistry but little is known about the profile of these visits. Objective: To evaluate the profile of patients aged between 0 and 13 years assisted at the Urgency Unit offered by FOAr, from 1997 to 2012, in order to quantify patients and procedures performed and identify the most frequently treatments performed. Material and method: In this observational transversal study, the reports of urgency service provided by the Integrated Clinical System were analyzed for the number of patients, treatments and type of procedures performed. The procedures were classified into seven categories: Diagnosis, Preventive, Anesthesia, Endodontic, Restorative, Surgical and Others. The data were organized and analyzed descriptively. Results: From 1997 to 2012, a total of 13,849 patients were treated in 25,786 visits and 86,279 procedures were conducted. A decrease in the number of patients assisted was observed. However, the number of appointments and the number of procedures did not decrease at the same ratio. Diagnosis procedures were the most frequent procedure performed, followed by preventive procedures. Restorative and endodontic treatments were the most frequent operative procedure performed. Dental surgeries were done less frequently. Conclusion: A profile change in the dental urgent treatment was observed throughout the years. Despite a reduction in the number of patients assisted, the number of visits and the amount of procedures performed remained stable. The procedures performed are in agreement with the profile of a dental urgent care clinic.

Resumo Introdução: Atendimentos de urgência são uma prática comum em Odontopediatria, porém pouco se sabe sobre o perfil desses atendimentos. Objetivo: Avaliar o perfil dos atendimentos de urgência de crianças de 0 a 13 anos de idade realizados na Clínica Infantil da FOAr, no período de 1997 a 2012, a fim de se quantificarem os pacientes e os procedimentos realizados no Serviço, além de identificar os tratamentos mais realizados. Material e método: Neste estudo transversal observacional, os relatórios desse Serviço, fornecidos pelo Sistema Integrado de Clínicas, foram analisados quanto ao número de pacientes, aos atendimentos e ao tipo de procedimentos realizados. Os procedimentos foram classificados em sete categorias: Diagnóstico, Preventivos, Anestesia, Endodônticos, Restauradores, Cirúrgicos e Outros. Esses dados foram tabulados e submetidos a uma análise descritiva. Resultado: De 1997 a 2012, foi atendido um total de 13.849 pacientes e foram realizados 25.786 atendimentos e 86.279 procedimentos. Houve diminuição do número de pacientes atendidos a partir de 2001, mas o número de consultas e de procedimentos não diminuiu na mesma proporção. Observou-se que, durante o período de 2007 a 2012, os procedimentos de diagnóstico foram os mais realizados, seguidos pelos preventivos. Dentre os procedimentos operatórios, o mais realizado foi o restaurador, seguido dos endodônticos. Procedimentos cirúrgicos estão entre os menos realizados. Conclusão: Conclui-se que houve uma mudança no perfil dos atendimentos dentro desse Serviço. Apesar de haver uma redução no número de pacientes atendidos, o número de consultas e a quantidade de procedimentos realizados permaneceram estáveis. Os procedimentos realizados estão de acordo com o perfil do Serviço de Urgência.
Treatment profile at dental urgent care clinic for children and teenagers from Faculdade de Odontologia de Araraquara (FOAr) – UNESP
Keywords: Health services; pediatric dentistry; health profile; Serviços de saúde; Odontopediatria; perfil de saúde